Improvement of Physical Training of Students Through the Means of Pouches Sport (Workout) (Eurasian Journal of Humanities and Social Sciences, 2022)
Organizing the construction of the car plant in the flow method of calendar plan modeling, creating a methodology for developing a calendar plan, identifying technical and economic advantages and applying them in design practice.